If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -9) + -1(x + 1) = 0 Reorder the terms: (-9 + 5x) + -1(x + 1) = 0 Remove parenthesis around (-9 + 5x) -9 + 5x + -1(x + 1) = 0 Reorder the terms: -9 + 5x + -1(1 + x) = 0 -9 + 5x + (1 * -1 + x * -1) = 0 -9 + 5x + (-1 + -1x) = 0 Reorder the terms: -9 + -1 + 5x + -1x = 0 Combine like terms: -9 + -1 = -10 -10 + 5x + -1x = 0 Combine like terms: 5x + -1x = 4x -10 + 4x = 0 Solving -10 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 4x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 4x = 0 + 10 4x = 0 + 10 Combine like terms: 0 + 10 = 10 4x = 10 Divide each side by '4'. x = 2.5 Simplifying x = 2.5
| 4z=50.8 | | 12k^2+4k=21-7k | | (z^2)-z+5=0 | | 9x+6y=4x-5y | | 56=1.4t | | 49y^2=36 | | 72+(X*.20)=70 | | 5x+2y-5z=40 | | 7log(9x-5)=1 | | 35.00+0.75x=50.00 | | 7x-27=8 | | 35.00+0.75=50.00 | | s^2-4s-3=0 | | x=1/2+2 | | x=1/2-2 | | 0=1/2-2y | | .1111x=2x-x^2 | | 5(-0.2)+1=x | | 9x-23=9x+-8 | | 6(5y+1)-5y=1 | | z^2-5z+3=0 | | 60x+40=700 | | 60+40=700 | | x^2+x+9=(3x+2)(x-8) | | 35x+25=700+40 | | 6+3c=38-c | | 7x+3=6x+26 | | f(x)=5x^3+15x^2-120x | | 5x+5-6x=2x+17-7x | | 35x(25+40)=700 | | 9y+7=31+y | | y-2=-3(x-5) |